Identifikasi dan Prevalensi Kejadian Ringworm pada Sapi Bali (IDENTIFICATION AND PREVALENCE OF RINGWORM CASE ON BALI CATTLE) - Putriningsih, Putu Ayu Sisyawati; Widyastuti, Sri Kayati; Arjentinia, I Putu Gede Yudhi; Batan, I Wayan (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
Ringworm is an infectious skin disease caused by dermatophytes and can infected various of animals,including cattle. This disease is not only able to cause high economic losses in the farm but also zoonotic.The aims of this study were to conduct a preliminary study of ringworm in Bali cattle of especieally toidentify the causes and clinical lesion and also its prevalence. Samples which suspected ringworm werecollected from Badung and Buleleng Regency, Bali Province. Skin lesion of suspected infected by ringwormwere observed, recorded, and documented. Skin scrapings and hair was taken for direct microscopicexamination for the presence of fungal element (hyphae or arthrospora). Skin scrapings and hair sampleswere dropped with KOH 10% and China ink (Parker®) then were left at room temperature for 10-15minutes. Samples were observed by microscope with a magnification of 100X and 400X gradually. Thedata were analyzed descriptively. In skin scraping and hair samples were found fungal elements, butcannot identify the species. Clinical lesions are seen in Bali cattle infected with ringworm include white,gray, or black (hyperpigmentation) circular alopecia accompanied by hyperkeratosis, scale, and crusting.Ringworm prevalence on Bali cattle in Bali is about 1.48%.. The prevalence rates associated with weatherfactors and maintenance system.
Keywords: ringworm, Bali cattle, prevalence, identification, zoonotic